High rates of alcohol consumption and related harm at schoolies week: a portal study - Dan I. Lubman; Nic Droste; Amy Pennay; Shannon Hyder; Peter Miller (Elsevier, 2014)
Abstract Objective: To investigate alcohol consumption, substance use and risky and harmful behaviour among young people attending 'schoolies' week in Victoria. Methods: Breathalyser tests and brief surveys (n=558) measuring alcohol, energy drink and illicit drug use, and experience of aggressive incidents, alcohol‐related injury and unprotected sex, were undertaken with young people attending schoolies week in Lorne and Torquay. Results: Schoolies reported consuming a mean of 8.8 drinks in the current session, with a mean blood alcohol count (BAC) of 0.05; 18.3% recorded a BAC of greater than 0.08. One in six participants had consumed alcohol with energy drinks; 7.7% reported using illicit substances. Participants who co‐consumed alcohol and energy drinks recorded a higher BAC than alcohol‐only users. One in five participants had experienced alcohol‐related harm at schoolies week, including aggressive incidents, alcohol‐related injury and engagement in unprotected sex. Each alcoholic drink consumed increased the potential for involvement in aggressive incidents by 8% and alcohol‐related accidents/injuries by 5%; illicit drug use was associated with six times the likelihood of engaging in unprotected sex with a non‐partner. Conclusions and implications: Excessive alcohol consumption and experience of related harms are common among young people attending schoolies week. Harm reduction initiatives targeting schoolies week should focus on the consequences of excessive alcohol consumption, illicit drugs and the co‐consumption of alcohol and energy drinks.